THE INFLUENCE OF INTELLIGENT INTELLECTUAL, EMOTIONAL AND SPIRITUAL ON ACCOUNTING UNDERSTANDING - Heri Kurniansyah; Nia Daveta (Proceeding International Conference on Information Technology and Business, 2018)
This study analyzes the influence of intelligent Intellectual, Emotional and Spiritual variables on Accounting Understanding. The primary data used in this study were obtained from the results of questionnaires for the Accounting Study Program Students of STIE Mitra Lampung in 2016. The sample was 41 respondents with the Slovin Sampling method. The analysis technique used is multiple regression to examine the effect of several independent variables on the dependent variable. The results of this study indicate that Intellectual Intelligence has no significant effect on Accounting Understanding. While Emotional and Spiritual Intelligence has a positive and significant effect on Accounting Understanding. the results of this study show 95.2% Accounting Understanding is influenced by Intellectual, Emotional and Spiritual Intelligence and the remaining 4.8% is influenced by other factors.Keywords: Intellectual Intelligence, Emotional, Spiritual and Accounting Understanding